Reading Comprehension in Older Adults—Effects of Age, Educational Level, and Reading Habits - Bernardo Riffo; Carlos Rojas; Andrea Helo; Mónica Véliz; Paula Urzúa; Gloria Gutierrez; Ernesto Guerra (Journal of Intelligence)
Older adults in the third-age group (60–79 years) maintain reading comprehension skills similar to those of younger adults, but little is known about individuals in the fourth age (80+ years). This study investigates differences in reading comprehension in a between-group design. We evaluated a sample of 150 older adults, comprising 86 third-age and 64 fourth-age participants. We examined the influence of sex, cognitive functioning, formal education, self-perceived reading difficulties, and reading habits on their text comprehension abilities. The results show that fourth-age adults have a significant decline in reading comprehension compared to third-age adults. Strong reading habits were positively associated with better comprehension across both groups, suggesting that regular reading may buffer against age-related cognitive decline. Poor readers read less frequently and perceived greater difficulty with the tasks. Cognitive functioning and education did not significantly influence comprehension—possibly due to the generally low education levels in the sample. However, strong reading habits appeared to compensate for these limitations. These findings suggest a potential protective role of lifelong reading habits and highlight the need for interventions to support reading skills in older adults, especially those with lower educational backgrounds. Future research should explore these dynamics further to enhance cognitive resilience in the oldest populations.